IMPLEMENTASI KEBIJAKAN PEMBINAAN DISIPLIN APARATUR PEMERINTAH DAERAH DI DINAS KEPENDUDUKAN DAN CATATAN SIPILKABUPATEN HALMAHERA UTARA - GAMSUNGI, RIVI; Ruru, Joorie M; Pombengi, Jericho D (JURNAL ADMINISTRASI PUBLIK, 2015)
This study aimed to determine the development of policy implementation disciplinegovernment officials / civil servants in the Department of Population and CivilRegistration of North Halmahera, and the impact of the implementation of that policyto increase discipline of local government officials.This study used qualitative methods. The informants are all local government officialsin the Department of Population and Civil Registration of North Halmahera as manyas 13 people. Instruments in this study is the researchers themselves, while collectingdata using interview techniques. Data was analyzed using qualitative analysistechniques interactiveModel of miles hubernannThe results of the study provide conclusions: (1) the implementation of civil servicediscipline policy guidance to local government officials have been done with goodviews of several aspects: the high commitment of the leadership to implement thispolicy, any communication or sosialilisasi effective civil service disciplinary rules toemployees, concrete efforts to increase the awareness of employees to carry out theprovisions of civil service discipline and creating a culture of discipline, and theirenforcement consistently disciplined for violation of obligations and prohibitions. (2)Implementation of policies fostering civil discipline has a positive impact onimproving the discipline of local government officials have seen improved adherenceand compliance officers against liability provisions and restrictions that apply to civilservants.Based on the conclusions of the research results presented suggestions: (1) theimplementation of development policies aperture discipline local government shouldbe directed at increasing awareness that will happen purely on self-discipline eachapparatus; (2) Implementation of policy guidance apparatus discipline will provide amore significant positive impact on the improvement of discipline only if accompaniedby an increase in the welfare of the key aparatur.Kata: coaching discipline policyapparatus / PNS